North American Social Report - Michalos, Alex C. author. aut Link
XV, 219 p.
Keywords: For readers who intend to read this volume without reading the ftrst, some introductory remarks are in order about the scope of the work and the strategy used in all ftve volumes to measure the quality of life. In the ftrst chapter of Volume I, I reviewed the relevant recent literature on social indicators and social reporting, and explained all the general difficulties involved in such work. It would be redundant to repeat that discussion here, but there are some fundamental points that are worth mentioning. Readers who fmd this account too brief should consult the longer discussion. The basic question that will be answered in this work in this: Is there a difference in the quality of life in Canada and the United States of America, and if so, in which country is it better? Alternatively, one could put the question thus: If one individual were randomly selected out of Canada and another out of the United States, would there be important qualitative differences, and if so, which one would probably be better off? To simplify matters, I often use the terms 'Canadian' and 'American' as abbreviations for 'a randomly selected resident' of Canada or the United States, respectively.